Pseudo-Kaposi's Sarcoma Because of Suction-Socket Lower Limb Prosthesis - Trindade, F (2016)
Pseudo-Kaposi sarcoma is a benign reactive vascular proliferation mainly involving the lower legs, which can be related to acquired chronic venous insufficiency or congenital arteriovenous malformations. In its most common presentation, acroangiodermatitis is seen in patients with chronic venous insufficiency of the lower limbs as an exaggeration of the stasis dermatitis. However, rare reports of acroangiodermatitis include descriptions in amputees (especially in those with poorly fitting suction-type devices), in patients undergoing hemodialysis (with lesions developing distally to arteriovenous shunts) and in patients with paralyzed legs. We report on a 28 year-old-male who presented pseudo-Kaposi's sarcoma in an amputation stump because of suction-socket lower limb prosthesis.